Apropiación y alienación: consideraciones hermenéutico-existenciales a propósito de la Pastoral Americana de Philip Roth (2013)
Starting from a basic formulation of relevant elements of Heidegger’s phenomenological hermeneutics, this article proposes a reading of the work of the american writer Philip Roth, which earned him a Pulitzer Prize in 1989, entitled American Pastoral -- The main purpose of this reading is to show how elementary existential phenomena like being-away (Wegsein), staying-awake (Wachsein), being-there (Dasein) allow an appropriate articulation of meaning of the work of Roth, in which it declares his particular existential commitment